Research into the process of preparation of Ukrainian coal by the oil aggregation method - Biletskyi, V. S.; Molchanov, P.; Sokur, M.; Gayko, G.; Savyk, V.; Orlovskyy, V. M.; Liakh, M.; Yatsyshyn, T.; Fursa, R. (Технологический центр, 2017)
We conducted a study into concentration of Donetsk coal with varying degrees of coalification – anthracite and grade G – by the method of oil aggregation. We determined the character of impact of the following factors on the results of oil aggregation of coal: the ash content of original coal, pulp agitation duration, pulp density, consumption and type of reagent-binder. The research demonstrated a possibility of effective preparation of finely- and thinly dispersed Donetsk coal the size of 0–0.1; 0–1(2) mm and ash content from 10–15 % to 65–70 % by the method of oil aggregation. In this case, it was established that with an increase in the ash content of original coal, the process of oil aggregation displays a capacity of self-leveling. By reducing the speed of aggregation, it is possible to attain practically stable technological results over the entire examined range of ash content of original coal – from 10–15 % to 65–70 %. Obtained results substantiate the possibility of employing the process of oil aggregation for the re-preparation of waste, in particular, waste of flotation and gravitation separation of coal preparation.

Досліджено збагачення донецького вугілля різного ступеня вуглефікації масляною агрегацією. Встановлено вплив на результати процесу зольності вугілля, тривалості агітації, густини пульпи, витрат і виду реагенту. Показано можливість ефективного збагачення вугілля крупності 0–0,1 (2) мм, зольності 10–70 % і самовирівнювання масляної агрегації при збільшенні зольності. Обгрунтовано застосування масляної агрегації для перезбагачення відходів флотації.
Keywords: oil aggregation; coal preparation; ash content of coal; aggregation; self-leveling of oil aggregation; масляна агрегація; збагачення вугілля; зольність вугілля; агрегатоутворення; самовирівнювання масляної агрегації